Synthesis, biological profiling and mechanistic studies of 4-aminoquinoline-based heterodimeric compounds with dual trypanocidal–antiplasmodial activity. Issue 16 (15th August 2015) - Sola, Irene; Castellà, Sílvia; Viayna, Elisabet; Galdeano, Carles; Taylor, Martin C.; Gbedema, Stephen Y.; Pérez, Belén; Clos, M. Victòria; Jones, Deuan C.; Fairlamb, Alan H.; Wright, Colin W.; Kelly, John M.; et al.
Graphical abstract: Abstract: Dual submicromolar trypanocidal–antiplasmodial compounds have been identified by screening and chemical synthesis of 4-aminoquinoline-based heterodimeric compounds of three different structural classes. In Trypanosoma brucei, inhibition of the enzyme trypanothione reductase seems to be involved in the potent trypanocidal activity of these heterodimers, although it is probably not the main biological target. Regarding antiplasmodial activity, the heterodimers seem to share the mode of action of the antimalarial drug chloroquine, which involves inhibition of the haem detoxification process. Interestingly, all of these heterodimers display good brain permeabilities, thereby being potentially useful for late stage human African trypanosomiasis. Future optimization of these compounds should focus mainly on decreasing cytotoxicity and acetylcholinesterase inhibitory activity.